1993
DOI: 10.1002/tera.1420480106
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic development of the mammalian caudal Neural Tube

Abstract: In the literature, some controversy still exists about the embryonic developmental processes involved in the formation of the caudal neural tube. Therefore, a three-dimensional and histological study concerning the normal development of the caudal neural tube was performed on both mouse and human embryos. Three developmental processes can be distinguished in caudal neural tube development: caudal neuropore closure, secondary neurulation, and degeneration and differentiation of the secondary neural tube. Caudal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 13 publications
4
80
0
7
Order By: Relevance
“…The caudal eminence gives rise to the caudal portion of the digestive tube, blood vessels, and the future somites of the S1-2 vertebral level and below-and eventually the spinal cord. [10][11][12][13] The caudal eminence fuses with the caudal neuropore and forms a solid cellular mass called the neural cord at POD 26, which then undergoes cavitation and connects to the central canal already present in the neural tube. By this process of cavitation, the solid neural cord transforms into a hollow secondary neural tube and fuses with the neural tube formed by primary neurulation into a continuous entity.…”
Section: Discussion Embryonic Process Of Neural Tube Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The caudal eminence gives rise to the caudal portion of the digestive tube, blood vessels, and the future somites of the S1-2 vertebral level and below-and eventually the spinal cord. [10][11][12][13] The caudal eminence fuses with the caudal neuropore and forms a solid cellular mass called the neural cord at POD 26, which then undergoes cavitation and connects to the central canal already present in the neural tube. By this process of cavitation, the solid neural cord transforms into a hollow secondary neural tube and fuses with the neural tube formed by primary neurulation into a continuous entity.…”
Section: Discussion Embryonic Process Of Neural Tube Formationmentioning
confidence: 99%
“…7,12 It is estimated that secondary neurulation continues until at least postovulatory Week 7. 13 In short, secondary neurulation occurs in 4 steps.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Neurulation, starting at the 3 week embryonic age, is responsible for formation of the neural tube by progressive closure of the neural plate and its separation from the overlying ectoderm. The distal cord develops from a caudal cell mass that forms from neural epithelium and notochord caudal to the primary neural tube.…”
Section: Discussionmentioning
confidence: 99%
“…This cord subsequently becomes cavitated and connected with the more rostrally located neural tube. It has been shown that the medullary cord gives rise to the spinal cord caudal to the level of the 32nd to 34th somites (Nievelstein et al, 1993). This process is called secondary neurulation and is distinguished from primary neurulation that forms the brain and the most part of the spinal cord by means of neural tube closure.…”
Section: Development Of the Spinal Cordmentioning
confidence: 99%